2023
DOI: 10.3390/plants12132516
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Potato as a Key Crop for Food Security under the Conditions of Global Climate Change: A Review

Abstract: Sweet potato is one of the most economically important crops for addressing global food security and climate change issues, especially under conditions of extensive agriculture, such as those found in developing countries. However, osmotic stress negatively impacts the agronomic and economic productivity of sweet potato cultivation by inducing several morphological, physiological, and biochemical changes. Plants employ many signaling pathways to respond to water stress by modifying their growth patterns, activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 161 publications
0
9
0
Order By: Relevance
“…This indicates that the response of different tissue parts of these two plants to the drought environment was different. W. trilobata and W. chinensis exhibited different endogenous hormones in the two simulated drought conditions, indicating different adaptation mechanisms: The hormone contents in aboveground parts and underground parts of W. trilobata ( Table 3 ) followed ABA > IAA > GA during PEG-simulated drought [ 44 ]. The hormone content in aboveground parts and underground parts of W. chinensis followed IAA > ABA > GA during PEG-simulated drought; the distribution pattern of IAA > ABA > GA in the aboveground and underground of the two plants under natural drought was the same ( Table 3 ) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the response of different tissue parts of these two plants to the drought environment was different. W. trilobata and W. chinensis exhibited different endogenous hormones in the two simulated drought conditions, indicating different adaptation mechanisms: The hormone contents in aboveground parts and underground parts of W. trilobata ( Table 3 ) followed ABA > IAA > GA during PEG-simulated drought [ 44 ]. The hormone content in aboveground parts and underground parts of W. chinensis followed IAA > ABA > GA during PEG-simulated drought; the distribution pattern of IAA > ABA > GA in the aboveground and underground of the two plants under natural drought was the same ( Table 3 ) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Field trials conducted in different agro-ecological regions in Kenya have revealed that the three mutants have better tolerance to these diseases than their respective parents [ 56 ]. On the other hand, an attempt to increase β carotene content by co-expression of transgenes for deoxy-d-xylulose-5-phosphate synthase and bacterial phytoene synthase in cassava resulted in reduced dry matter and starch content, despite a 15–20-fold increase in carotenoids [ 57 ].…”
Section: Root and Tuber Cropsmentioning
confidence: 99%
“…Sweet potato ( Ipomoea batatas (L.) Lam—Convolvulaceae) is the other most important root and tuber crop cultivated worldwide, ranking seventh overall in terms of production [ 57 ] and having considerable potential to reduce the Global Hunger Index, particularly in sub-Saharan Africa, the Pacific Islands, and parts of Asia [ 58 ]. Hexaploidy and self- and cross-incompatibility in sweet potato introduce difficulties in using both traditional breeding and genomic approaches for their improvement.…”
Section: Root and Tuber Cropsmentioning
confidence: 99%
“…1 . Sweetpotato is well-suited to tropical and subtropical climates, contributing significantly to the food supply in regions like Southeast Asia ( Sapakhova et al, 2023 ). In many developing countries, sweetpotato is a vital component of subsistence farming, playing a crucial role in addressing food shortage issues in part of regions in history, as its nature of cold and drought tolerance, good adaptability to different climates, as well as reliable source of nutrition ( Fuglie, 2007 ).…”
Section: Introductionmentioning
confidence: 99%